THE SUBSTANCE OF THE PROHIBITION OF ALCOHOLIC BEVERAGES IN THE MANIFESTATION OF THE MAQASID AL-SHARI’A IN LAND OF PAPUA - Rohman, Baitur; Sultan, Lomba; Marilang, Marilang; Hasan, Hamzah (Jurnal Diskursus Islam, 2020)
This paper elaborated on the Substance of the Prohibition of Alcoholic Beverages in the Provincial Regulation of Papua Number 15 of 2013 concerning the Prohibition of the Production, Distribution, and Sales of Alcoholic Beverages in the Manifestation of Maqasid al-Shari’a in Papua. This type of research was qualitative empirical legal research with a normative theological approach, statute approach, and sociological approach. The results showed that the substance of the prohibition of alcoholic beverages in the Provincial Regulation of Papua Number 15/2013 which totally prohibited the production, distribution, sales, and consumption of alcoholic beverages was legally contrary to Presidential Decree Number 74 of 2013. Based on the principle of “Lex Superiori Derogad Lege Inferiori”, the Provincial Regulation of Papua Number 15 of 2013 could be ruled out by the Presidential Decree Number 74 of 2013. Therefore, the Ministry of Home Affairs canceled the Provincial Regulation Number 15 of 2013 because it violated the principle of the hierarchy of laws and regulations. Based on the perspective of maqasid al-shari’a, the regulation of alcoholic beverages in the Provincial Regulation of Papua was a necessity of daruriyyat. Thus, everything to make it happen was also daruriyyat.